Separation mechanism of asphalt rubber and improvement with microwave irradiation. (1st August 2022) - Yao, Zechen; Yang, Renfeng; Shi, Jierong; Zhang, Chunhai; Zhang, Yong
Highlights: Separation mechanism of asphalt rubber was analysed. Three particle size CRs, and three microwave times were used to produce binders. Irregularity of CR had an obvious benefit for improving storage stability. Microwave irradiation was conducive to improve storage stability. Abstract: This study aims to analyse the separation mechanism of asphalt rubber (AR) binder and the principle of improving storage stability by microwave irradiation. Based on an in-depth analysis of the terminal settling velocity of crumb rubber (CR) particles, Scanning electron microscopy and Fourier transform infrared spectroscopy were used to investigate the physical and chemical properties of CR with different particle sizes and microwave times. Separation and dynamic shear rheometer (DSR) tests were performed to evaluate the storage stability of the AR binders quantitatively. The results showed that the increase in the surface irregularity of CR particles had an obvious benefit for improving storage stability, which can directly reduce the particle terminal settling velocity, especially at low Reynolds numbers. CR with higher irregularity was also conducive to material exchange and reduction of density difference. The irregularity of the CR particles and the strength of the C-N functional group increased with microwave time roughly, which was beneficial for enhancing storage stability. Changes in the physical and chemical properties were more evident in the #20 CR particles after microwave irradiation. Separation and DSR tests showed that the storage stability improved with increased microwave time. The improvement of the AR binders with #20 coarse CR was relatively more remarkable, while the improvement of the AR binders with #80 fine CR was smoother. Notably, the CR density may be lower than the asphalt density.